Implementasi Jaminan Kehilangan Pekerjaan dalam Penanganan PHK di Dinas Ketenagakerjaan dan Transmigrasi Kabupaten Sukabumi - Nurhaliza Witriani; Rizal Amirulloh; Dine Meigawati (Universitas 17 Agustus 1945 Semarang, 2026)
The Job Loss Guarantee Program (Jaminan Kehilangan Pekerjaan/JKP) is a social protection scheme designed to support workers affected by employment termination. However, its implementation at the local level still faces significant challenges. This study aims to examine the implementation of the JKP program in handling layoffs at the Manpower and Transmigration Office of Sukabumi Regency. The research employs a qualitative descriptive approach, using observation, in-depth interviews, and documentation studies as data collection techniques. Data analysis is conducted using Edwards III’s policy implementation model, which focuses on communication, resources, disposition, and bureaucratic structure. The findings reveal that the implementation of the JKP program in Sukabumi Regency has not yet been optimal, as reflected in the low proportion of laid-off workers who successfully receive JKP benefits compared to the total number of layoffs. In terms of communication, policy information has been delivered formally and consistently, but its outreach and intensity remain limited. Resource constraints, particularly in human resources and budget allocation, also hinder effective implementation, despite adequate authority and supporting facilities. Meanwhile, implementers demonstrate a positive disposition and strong commitment, whereas bureaucratic structure issues persist due to the absence of specific standard operating procedures and fragmented institutional roles. This study concludes that strengthening communication, resources, and bureaucratic structure is essential to improve the effectiveness of JKP program implementation at the local level.